Studi Putusan Pengadilan dalam Kasus Wahl Clipper Corporation Melawan Distributor Merek Wahl di Indonesia - Julian P., Maeswadhita (Fakultas Hukum Universitas Islam Indonesia, 2021)
At the Central Jakarta District Court No. 57/Pdt.Sus- Merek/2015/PN Niaga Jkt.Pst. on December 17, 2015 which essentially rejected the Wahl Clipper Corporation lawsuit. The decision was strengthened by the result of cassation No. 444 K/Pdt.Sus-HKI/2016 on July 26, 2016 which essentially rejected the appeal filed by the Cassation Petitioner, namely Wahl Clipper Corporation itself. The case is still ongoing until the Review of Decision Number 1 PK/Pdt.Sus-HKI/2018 on January 16, 2018, the party who feels aggrieved, namely Wahl Clipper Corporation has new evidence that can strengthen the evidence that the Petitioner is really harmed by the Respondent ; The author wants to examine the problems in this Legal Case Study, namely: 1. Is the analysis of judges' considerations regarding well-known brands in Indonesia in the Wahl Clipper Corporation case correct based on Law No. 15 of 2001 concerning Marks and Law No. 20 of 2016 concerning Trademarks and Geographical Indications? 2. What are the legal consequences of the court's decision on the famous trademark lawsuit Number 444 K/Pdt.Sus- HKI/2016 in Indonesia?; After discussing and analyzing the trademark cancellation lawsuit between Wahl Clipper Corporation and Harry Sudjono, it can be concluded as follows: 1. The Supreme Court's decision Number 444K/Pdt.Sus-HKI/2016 regarding the Wahl Clipper Corporation's lawsuit against Harry Sudjono is inaccurate. 2. The decision of the Supreme Court Number 444K/Pdt.Sus-HKI/2016 which was ruled by the decision to be rejected, has no legal consequences. Because the judge rejected the Cassation application for the cancellation of the Mark.